Assessing the competitiveness of sheep production in selected states in Sudan - Elbadawi, Elsedig; Mohamed Arshad, Fatimah; Mohamed, Zainal Abidin; Ismail, Mohd Mansor (Canadian Center of Science and Education, 2013)
This paper aimed to evaluates the competitiveness of sheep production in North Kordofan and Gadarif states in Sudan. Primary data which was collected from survey questionnaire from tow states in 2010 to find cost of production, output, input price, government intervention etc. The Policy Analysis Matrix (PAM) methodology was used in this study to analyze the data. The findings of this study show that government interventions on sheep’s production in terms of taxes have negative impact on the competitiveness of sheep export in the selected states. The production shows a strong competitiveness. The results of DRC indicator suggest that Sudan enjoys comparative advantage in production of sheep in selected states. North Kordofan has proven to be more effective in saving the foreign exchange, followed by Gadarif. The international value added (IVA) indicted a positive foreign exchange earnings or savings. Exported live sheep coefficient of international competitiveness (CIC) implied that sheep export is profitable and internationally competitive. The recommends of this study government should; encourage sheep production, increase the level of output, improved sheep productivity and also government should reduce the tax from the sheep production.